(untitled) (International Seven Journal of Multidisciplinary, 2023)
The article identifies the elements and limitations considered for the effectiveness of multi-parentality, emphasizing the principle of affection for considering it a determining factor for the recognition of the socio-affective bond. It also discusses the procedures used to achieve the recognition of social-affective relationships, as well as the inheritance rights generated by this recognition. Our objective is to analyze the principle of affectivity and its relevance in the recognition of the socio-affective bond and, further, the possibility of accomplishment in the extrajudicial realm, highlighting the characteristics of multi-parentality and the succession effects generated after the established multi-parental bond. This article was developed using the hypothetical-deductive method, since the conclusions were deduced based on articles, literature and jurisprudence about affectivity and new family models. We were able to verify, then, that the multiparentality marked the new concept of family resulting from the transformations in civil law, because it broadened the understanding of paternal and maternal figures, which should not be determined only by the genetic factor, but by the relationship based on affection, love and care between family members. DOI: 10.56238/isevmjv1n1-001